Nutrient requirements in Hanwoo cows with artificial insemination: effects on blood metabolites and embryo recovery rate - Kang, Sung-Sik (J Anim Sci Technol, 2020)
Here, we investigated the effects of different nutrient requirements (NR) on blood metabolites, transferable embryo number after multiple superovulations with artificial insemination (AI), body condition score (BCS), and estrus cycle in Hanwoo cow. Nineteen Hanwoo cows were randomly divided into three groups (80%, 100%, and 120% NR, containing 6, 8, and 5 individuals, respectively) and fed based on the NR. In experiment 1, glucose, total cholesterol, triglyceride, blood urea nitrogen (BUN), aspartate aminotransferase (AST), alanine aminotransferase (ALT), non-esterified fatty acids (NEFA), albumin (ALB), and total protein (TP) were analyzed. In experiment 2, total number of recovered embryos and transferable embryos was examined after embryo recovery and multiple superovulations with AI. In experiment 3, body weight, BCS, and estrus cycle were examined. In experiment 1, total cholesterol was significantly different among the 80%, 100%, and 120% NR groups (126.5 ± 3.3, 152.6 ± 2.4, and 177.4 ± 1.8 mg/dL, respectively, p < 0.05). The triglyceride and BUN levels in the 120% NR group were significantly higher than those in the 80% and 100% groups (p < 0.05). The NEFA levels were significantly different among the 80%, 100%, and 120% NR groups (440.5 ± 18.2, 318.5 ± 23.1, and 195.1 ± 8.5 ЧEq/L, respectively, p < 0.05). The AST and TP levels in the 80% NR group were significantly lower than those in the 100% and 120% NR groups (p < 0.05). In experiment 2, the 120% NR group showed a higher percentage of transferable embryos than the 80% and 100% groups (p < 0.01). The mean body weight and BCS among the 80%, 100%, and 120% NR groups were significantly different (p < 0.05). The estrus cycle in the 80% NR group was delayed compared with the 100% and 120% NR groups (20.8 ± 0.2 and 21.2 ± 0.5 days, respectively). In conclusion, the blood metabolic tests proved that Hanwoo cows with 120% NR can produce a large number of transferable embryos. Thus, 120% NR is the appropriate feeding level for this type of cows as it results in the production of a large number of transferable embryos by multiple superovulations with AI.